KELANGSUNGAN HIDUP IKAN MAS (Cyprinus carpio L) YANG DIBERI PAKAN EKSTRAK BAWANG PUTIH (Allium sativum) DAN DI INFEKSI Aeromonas hydrophila - Lukistyowati, Iesje; Kurniasih, Kurniasih (Jurnal Perikanan dan Kelautan, 2011)
The aim of a research were to investigate the effectiveness of garlic extractmixed with feed given 30 days in encharging common carps after challen with againstAeromonas hydrophila with density of 106 cell/ml. This research conducted by usingcomplete random design with dose addition of garlic extract to feed were controlpositive, control negative, P1 (2,5%), P2 (5%), and P3 (10%). In order to fine out theactive component of garlic extraction methode was adopted using 70% ethanol. Theextracted filtrates were separated using the spectrophotometrical chromatrographymethod (GC-MS) and thin-layered chromatography. Identification of the maincomponents found in the ethanol extract of garlic revealed 13 components but the onethat served as antimicrobial was C6H10S2 CAS disulphide di 2-propenyl(CAS)/(Diallyldisulfide) with and area of 16,95%. Beside the result of thin layeredchromatography showed that garlic extact contained sapononin which is harmful toaquatic animals. Percentage of survival rate P3 (10%) after infected after withAeromonas hydrophila was different compare witn control positive. The highsurvival shown on P3 (10%) concentration with 70%, P1 60%, control negative 60%and P2 30%. Fourteen days after injection the cut cause by Aeromonas hydrophilaclose and the fish recuperated as shown by their lively movement.